Classification criteria for Sjögren's syndrome: a revised version of the European criteria proposed by the American-European Consensus Group. Issue 6 (1st June 2002) - Vitali, C; Bombardieri, S; Jonsson, R; Moutsopoulos, H M; Alexander, E L; Carsons, S E; Daniels, T E; Fox, P C; Fox, R I; Kassan, S S; Pillemer, S R; Talal, N; et al.
Abstract : Classification criteria for Sjögren's syndrome (SS) were developed and validated between 1989 and 1996 by the European Study Group on Classification Criteria for SS, and broadly accepted. These have been re-examined by consensus group members, who have introduced some modifications, more clearly defined the rules for classifying patients with primary or secondary SS, and provided more precise exclusion criteria.